ISOLASI DAN PENENTUAN STRUKTUR MOLEKUL DARI TANA MAN OBAT TRADISIONAL SMILAX CORDIFORIA - Muhammad Hanafi (Research Center for Chemistry - LIPI, 1996)
A research was carried out to isolate the constituents of Smilax cordiforia trunk bark. It is a famous medicinal plant in Mexico, used as weight control. The isolation methods were carried out by maceration in ether, and remaceration in methanol, and then both of crude extracts were purified by using combined chromatography technique. In the purification and identitification of the ether extract two compounds as steroid saponins, 3-B-O -B-D-glucopyranosyl sitosterol (1) and a mixture of 6-O-palmitoyl-glucopiranosil sitosterot, 6-0stearylglucopyranosyl sitosterol and 6-0arachidoyl-glucopyranosyl sitosterol (2) were obtained, which also have been isolated from other medicinal plants. Isolation from methanol extract resulted in four known substance of phenolic derivatives, identified as afilbin (3) isoastilbin (4), engelitin (5). and chlorogenic acid (C). engelitin demonstrated antifungal activity, astilbin and chlorogenic acid showed antifungal, antibacterial, and antiviral activities. Chlorogenic acid also exhibited antimutagenic, antitumour and antioxcidant activities. Their molecular structures were detemined on the basis of combied spectroscopic methods including two dimensional NMR (2D NMR).